2022
DOI: 10.1155/2022/1998808
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening, Antioxidant, and Antimicrobial Activities of Seven Underinvestigated Medicinal Plants against Microbial Pathogens

Abstract: Background. Plants are a rich source of therapeutic compounds that have tremendous applications in the pharmaceutical industry. This study aimed to identify the phytochemicals present in the seven selected medicinal plants as well as their antioxidant and antimicrobial activities. Methods. Phytochemical screening, total phenolic, and flavonoid contents were determined using standard methods. The antioxidant activity of plant extracts was determined using 2, 2-diphenyl-1-picrylhydrazyl (DPPH), hydroxyl (OH), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…The extracts were screened for steroids, and they were found in all the extracts. Steroids derived from medicinal plants are known to possess antibacterial and insecticidal properties [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The extracts were screened for steroids, and they were found in all the extracts. Steroids derived from medicinal plants are known to possess antibacterial and insecticidal properties [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the emergence of antifungal drug resistance in C. neoformans has increased rapidly [27]. Hence, the morbidity and mortality rates due to cryptococcosis caused by C. neoformans are increasing continuously.…”
Section: Discussionmentioning
confidence: 99%
“…There is a shift of focus to medicinal plants due to the increased antimicrobial resistance, severe adverse effects, high costs of synthetically available drugs and the community perception towards modern health care practice [33]. Many studies demonstrated that plant extracts are highly effective against bacterial microorganisms due to enormous kind of secondary metabolites [33,34,35].…”
Section: Discussionmentioning
confidence: 99%